Effect of Body Mass Index on Gastroesophageal Reflux Disease - Sabah Jalal Shareef (Advanced Medical Journal)
Background and objectives: The gastroesophageal reflux disease is a diagnostic and therapeutic challenge in surgery because of its complicated etiology and pathophysiology. Its incidence is increasing parallel with obesity throughout the world. This study tried to find a relation between body mass index and gastroesophageal reflux disease.